2017
DOI: 10.24930/1681-9004-2017-4-062-072
|View full text |Cite
|
Sign up to set email alerts
|

Stratigraphic significance of Devonian brachiopods of the Urals

Abstract: Поступила в редакцию 14.11.2016 г.; принята к печати 30.12.1016 г.В статье рассмотрена история становления региональной стратиграфической шкалы девонской системы Урала, исто-рически разработанной на основе изучения бентосной фауны (в основном брахиопод). В настоящее время она пред-ставлена следующими надгоризонтами (региоярусами) и горизонтами стратотипических областей (снизу вверх): мансийский (сарайнинский и саумский горизонты), витимский (вижайский и тошемский горизонты), юртищенский (карпинский и тальтийск… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The Baronskaya section is situated on the right bank of the Mezhevaya Utka River (right tributary of the Chusovaya River), 6.5 km from the river mouth. The Upper Frasnian deposits of the Askynian RS and the Lower Famennian deposits of the Makarovian RS are represented by limestones, dolomitized limestones with intercalations of marls, mudstones, clayey and calcareous-siliceous shales [9,10].…”
Section: Geological Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…The Baronskaya section is situated on the right bank of the Mezhevaya Utka River (right tributary of the Chusovaya River), 6.5 km from the river mouth. The Upper Frasnian deposits of the Askynian RS and the Lower Famennian deposits of the Makarovian RS are represented by limestones, dolomitized limestones with intercalations of marls, mudstones, clayey and calcareous-siliceous shales [9,10].…”
Section: Geological Settingmentioning
confidence: 99%
“…The Pershino section is located near the village of Pershino on the Rezh River, 10 km north of the town of Rezh. The massive limestones of the Upper Frasnian deposits of the Gubinskian RS and the detrital limestones and siltstones of the Lower Famennian deposits of the Shameyskian RS are exposed in the section [10,13].…”
Section: Geological Settingmentioning
confidence: 99%
“…In a toxicological study, mitotic figures were found in renal tissue [17,18]. In our laboratory, we examined many DPPs for interactions with tubulin [9].…”
Section: Introductionmentioning
confidence: 99%